Polyacrylate-GnRH Peptide Conjugate as an Oral Contraceptive Vaccine Candidate - Mohammad O. Faruck; Prashamsa Koirala; Jieru Yang; Michael J. D'Occhio; Mariusz Skwarczynski; Istvan Toth (MDPI AG, 2021)
Contraceptive vaccines are designed to elicit immune responses against major components of animal reproductive systems. These vaccines, which are most commonly administered via injection, typically target gonadotropin-releasing hormone (GnRH). However, the need to restrain animals for treatment limits the field applications of injectable vaccines. Oral administration would broaden vaccine applicability. We explored contraceptive vaccine candidates composed of GnRH peptide hormone, universal T helper PADRE (P), and a poly(methylacrylate) (PMA)-based delivery system. When self-assembled into nanoparticles, PMA-P-GnRH induced the production of high IgG titers after subcutaneous and oral administration in mice. PADRE was then replaced with pig T helper derived from the swine flu virus, and the vaccine was tested in pigs. High levels of systemic antibodies were produced in pigs after both injection and oral administration of the vaccine. In conclusion, we developed a simple peptide-polymer conjugate that shows promise as an effective, adjuvant-free, oral GnRH-based contraceptive vaccine.